2015
DOI: 10.1159/000441626
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Crossover Trial: The Effect of Inulin on Glucose Homeostasis in Subtypes of Prediabetes

Abstract: Background: Fermentable carbohydrates (FCHO) have been shown to improve insulin sensitivity in normoglycaemic and insulin-resistant subjects. However, there are no data on subjects with prediabetes. We aimed to investigate the effect of the FCHO inulin, on glucose homeostasis in subjects with prediabetes. Methods: In a double-blind and placebo-controlled crossover study, 40 volunteers with prediabetes were randomly allocated to take 30 g/day of inulin or cellulose for 2 weeks in a crossover trial, following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 42 publications
4
32
1
Order By: Relevance
“…A recent meta-analysis showed that inulin-type fructans reduce fasting blood glucose in T2D patients ( Liu et al, 2017 ). Moreover, in pre-diabetic subjects, inulin moderated insulin resistance in an impaired fasting blood subgroup ( Guess et al, 2016 ). A combined supplement of inulin and fiberol-2 (another type of soluble dietary fiber) induced in a reduction in blood lipids in hamsters with hyperlipidemia ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that inulin-type fructans reduce fasting blood glucose in T2D patients ( Liu et al, 2017 ). Moreover, in pre-diabetic subjects, inulin moderated insulin resistance in an impaired fasting blood subgroup ( Guess et al, 2016 ). A combined supplement of inulin and fiberol-2 (another type of soluble dietary fiber) induced in a reduction in blood lipids in hamsters with hyperlipidemia ( Huang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the individuals with higher insulin sensitivity were more susceptible to the detrimental effects of SFA. Furthermore, Guess et al ( 141 ) recently reported that 6 weeks of supplementation with the dietary fiber inulin (30 g/d) decreased HOMA-IR in IFG but not in IGT individuals. These results may indicate that inulin has beneficial effects in subjects with liver-IR rather than muscle-IR, as IFG individuals have often a more pronounced liver-IR.…”
Section: Differential Effect Of Macronutrients On Ectopic Fat In Distmentioning
confidence: 99%
“…In overweight/obese men, colonic infusions of SCFA appear to increase fat oxidation, energy expenditure and PYY release, and decrease adipose tissue lipolysis [ 43 ]. Inulin, a fructo-oligosaccharide prebiotic NDC which is readily fermented producing SCFA, has demonstrated beneficial effects on adiposity [ 44 ] substrate metabolism [ 45 ], insulin sensitivity [ 46 ] and appetite regulation [ 47 49 ] although the effects seen in humans are inconsistent and may be related to the levels of inulin intake [ 50 ]. A recent meta-analysis tentatively concluded that inulin-type fructans elicit a beneficial effect on lipid profiles and glucose metabolism [ 51 ].…”
Section: Introductionmentioning
confidence: 99%